2016
DOI: 10.3390/su8040384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effect of Recycled Asphalt Shingle (RAS) in Portland Cement Mortar

Abstract: Tear-off roofing shingle, referred to as Reclaimed asphalt shingle (RAS), is the byproduct of construction demolition and it is a major solid waste stream in the U.S. Reuse of this byproduct in road construction sector can contribute to the success of materials sustainability as well as landfill conservation. Ground RAS has similar particle distribution as sand and its major component includes aggregate granules, fibers, and asphalt. To promote the beneficial utilization of RAS, this study evaluates the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On further analysis of SEM images of this nature, networks of cracks with widths in the range 4-20 µm were evident in the ITZ between aged bitumen and geopolymer grout in the SFC specimens. This is a common mechanism reported in the literature [43] for materials incorporating cementitious-and bitumen-based materials. While this phenomenon may help to impede crack propagation in SFC materials and improve its energy-absorbing capacity [16,22,43,44], their presence will contribute to reduced levels of compressive strength.…”
Section: Sfc Characterisationmentioning
confidence: 66%
“…On further analysis of SEM images of this nature, networks of cracks with widths in the range 4-20 µm were evident in the ITZ between aged bitumen and geopolymer grout in the SFC specimens. This is a common mechanism reported in the literature [43] for materials incorporating cementitious-and bitumen-based materials. While this phenomenon may help to impede crack propagation in SFC materials and improve its energy-absorbing capacity [16,22,43,44], their presence will contribute to reduced levels of compressive strength.…”
Section: Sfc Characterisationmentioning
confidence: 66%
“…Moreover, they observed a reduction in the optimal virgin binder content from 5.77% to 4.77% with a 5% shingle addition. Another study has shown that the grounded shingle was used in cement mortar and the fiber in the shingle helps to gain the strength of concrete [ 17 ]. Cooper et al [ 18 ] checked the concentration of asphaltene in the extracted aged binder from the shingle.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many pavement materials have reached the end of their service life and have been abandoned in the city (Figure 1). Therefore, developing more effective and durable recycling technologies to rejuvenate this waste asphalt concrete is important for sustainable urban construction [4][5][6].…”
Section: Introductionmentioning
confidence: 99%